Community Perceptions of the Impact of Marine Sand Mining Activities in the Riau Islands Province - Bahri, Samsul; Ismail, Khodijah; Habibah, Sayyidah Nur (Faculty of Fisheries and Marine, Universitas Riau, 2024)
This study aims to determine the perceptions of local communities towards marine sand mining activities in the Kepulauan Riau Province. Considering the region's dominance, Kepulauan Riau has great potential for sand mining in terms of quality and quantity. The population dynamics and high development today encourage an increased need for sand. Therefore, sand mining businesses have become social, economic, and ecological. This research uses a descriptive qualitative approach with an interview method with 60 respondents. Multiple linear regression analysis was used to predict perceptions based on social, economic, and ecological variables. The results showed that social aspects (coefficient value of 0.809) strongly influenced the sustainability of mining activities compared to ecological aspects (0.271) and economic aspects (-0.045). This finding shows that if mining activities can create good social conditions in local communities, sand mining activities can continue. However, these social conditions are related to the ecological impacts caused by mining